Drought, desertification in Tay Nguyen territory associated with climate change scenarios - Dan, Nguyen Lap; Hieu, Nguyen Trong; Lan, Vu Thi Thu (Vietnam Journal of Earth Sciences, 2014)
In recent years, under the impact of climate change, increasing deforestation and leveling soil, the natural flows regulating ability of river basins in Tay Nguyen has been declining strongly. Tay Nguyen has four major river systems:the upstream of Se San river, the upstream of Srepok river, the upstream of Ba river and the upstream of Dong Nai river. Tay Nguyen also has an abundant water resource, however, in dry season drought occurs consecutively having widespread influences. The drought is rarely the direct cause of human loss but social – economic and environmentaldamage caused by drought is significantly, especially it leads to desertification. In this study, the authors will analyze and assess the current status of drought and desertification in Tay Nguyen associated with climate change scenarios in the 21st century, proposing solutions to minimize and to respond to drought and desertification in Tay Nguyen.Just in time (1990 - 2000) in Tay Nguyen territory, drought occurred in 1994, 1995, 1996, 1997 and 1998 droughtprone rice area from 2,000 ha to 130.000ha each crop. In 1998, drought-prone coffee area was 74,400ha, 770,000 people are the lack of water in this drought.Drought had a great influence on the production winter-spring at the end of the 2012-2013, early summer-autumn in 2013 and water of the people in the provinces of Dak Lak, Dak Nong, Gia Lai, Kon Tum.Results of expected impacts of climate change to drought and desertification showed appearance of droughts and desertification gradually increase over time in 2020, 2050, 2100 on areas in Tay Nguyen. Thus, proposing solutions to minimize drought and desertification in Tay Nguyen territory including: construction of appropriate plant structure, modern irrigation technologies, water saving, hardened concrete canal systems, increased regulation of water throughgenerating additional downstream flow of the irrigation water source to meet the summer collection season. Organization of closely manage water resources and enhancing information, dissemination to local understand the drought response.